Cerium oxide nanoparticles administration during machine perfusion of discarded human livers: A pilot study. Issue 7 (19th April 2022) - Del Turco, Serena; Cappello, Valentina; Tapeinos, Christos; Moscardini, Aldo; Sabatino, Laura; Battaglini, Matteo; Melandro, Fabio; Torri, Francesco; Martinelli, Caterina; Babboni, Serena; Silvestrini, Beatrice; Morganti, Riccardo; et al.
Abstract: The combined approach of ex situ normothermic machine perfusion (NMP) and nanotechnology represents a strategy to mitigate ischemia/reperfusion injury in liver transplantation (LT). We evaluated the uptake, distribution, and efficacy of antioxidant cerium oxide nanoparticles (nanoceria) during normothermic perfusion of discarded human livers. A total of 9 discarded human liver grafts were randomized in 2 groups and underwent 4 h of NMP: 5 grafts were treated with nanoceria conjugated with albumin (Alb‐NC; 50 µg/ml) and compared with 4 untreated grafts. The intracellular uptake of nanoceria was analyzed by electron microscopy (EM) and inductively coupled plasma–mass spectrometry (ICP‐MS). The antioxidant activity of Alb‐NC was assayed in liver biopsies by glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) assay, telomere length, and 4977‐bp common mitochondrial DNA deletion (mtDNA 4977 deletion). The cytokine profile was evaluated in perfusate samples. EM and ICP‐MS confirmed Alb‐NC internalization, rescue of mitochondrial phenotype, decrease of lipid droplet peroxidation, and lipofuscin granules in the treated grafts. Alb‐NC exerted an antioxidant activity by increasing GSH levels (percentage change: +94% ± 25%; p = 0.01), SOD (+17% ± 4%; p = 0.02), and CAT activity (51% ± 23%; p = 0.03), reducing the occurrence of mtDNA 4977 deletion (−67.2% ± 11%; p = 0.03), but did not affect cytokine release. Alb‐NC during ex situ perfusion decreased oxidative stress, upregulating graft antioxidant defense. They could be a tool to improve quality grafts during NMP and represent an antioxidant strategy aimed at protecting the graft against reperfusion injury during LT.